Does Employer Branding Influence Retention? Mediating Role of Engagement among Young-Gen Worker in Jakarta - Annisa Syafira Efrial; Debora Justice Valentina; Ary Priambodo (CV. Ulil Albab Corp, 2026)
In an increasingly competitive employment landscape, retaining young generation employees has become a growing challenge for organizations, particularly as younger workers demonstrate higher mobility and changing workplace expectations. This study examines the relationship between employer branding, employee engagement, and employee retention among young generation formal workers in the Jakarta area. The study investigates the mediating role of employee engagement in the relationship between employer branding and employee retention. A quantitative approach was employed using primary data collected through self-administered questionnaires distributed to 244 respondents selected through purposive sampling. The data were analyzed using PLS-SEM. The findings reveal that employer branding significantly enhances employee engagement, indicating that young employees tend to feel more emotionally connected and actively involved when organizations are perceived as attractive and supportive workplaces. Employee engagement also significantly influences employee retention. However, employer branding does not directly influence employee retention. Instead, employee engagement fully mediates the relationship between employer branding and employee retention. These findings suggest that organizations should focus not only on building a strong employer image but also on creating meaningful work experiences that strengthen employees’ emotional attachment and commitment to remain within the organization.